Chronotype Genetic Variant in PER2 is Associated with Intrinsic Circadian Period in Humans - Chang, Anne-Marie (Sci Rep, 2019)
The PERIOD2 (PER2) gene is a core molecular component of the circadian clock and plays an important role in the generation and maintenance of daily rhythms. Rs35333999, a missense variant of PER2 common in European populations, has been shown to associate with later chronotype. Chronotype relates to the timing of biological and behavioral activities, including when we sleep, eat, and exercise, and later chronotype is associated with longer intrinsic circadian period (cycle length), a fundamental property of the circadian system. Thus, we tested whether this PER2 variant was associated with circadian period and found significant associations with longer intrinsic circadian period as measured under forced desynchrony protocols, the ‘gold standard’ for intrinsic circadian period assessment. Minor allele (T) carriers exhibited significantly longer circadian periods when determinations were based on either core body temperature or plasma melatonin measurements, as compared to non-carriers (by 12 and 11 min, respectively; accounting for ~7% of inter-individual variance). These findings provide a possible underlying biological mechanism for inter-individual differences in chronotype, and support the central role of PER2 in the human circadian timing system.